EFFECTIVENESS OF THE DRUGS CLEAN VILLAGE PROGRAM (SHINING VILLAGE) IN PADANG PELASAN VILLAGE, LUBUK GILANG, LAWANG AGUNG, AIR PERIUKAN DISTRICT, SELUMA DISTRICT - Afrianto; Bobby Mandala Putra; Hernowo Novi Yanto (Indonesian Journal of Social Sciences, Policy and Politics, 2025)
Bersinar Village is an effort to stop and deal with drug abuse in a village that is managed independently by the village government and the village community. The focus of this research is to look at the effectiveness of the drug clean village program and reduce the number of drug abuse cases in the villages of Padang Pelasan, Lubuk Gilang, and Lawang Agung. This research aims to gain an understanding and deepen the success of the Shining Village program with the hope of providing recommendations that can increase the effectiveness and sustainability of the Shining Village program. This type of research is descriptive qualitative. Based on the results of research conducted by researchers in the three villages that I studied, namely Padang Pelasan, Lubuk Gilang, and Lawang Agung villages, it can be said to be effective even though the eight indicators of success in implementing the drug-free village program have not been fully implemented in implementing the drug-free village program. Know from the results of observations, interviews, and also documentation.